Idiopathic intracranial hypertension leading to bilateral optic atrophy in a patient with recent COVID-19 infection: a case report - Yarky, Anu; Kumar, Vipan; Chauhan, Nidhi; Sharma, Priyesh (International Journal of Advances in Medicine, 2021)
Neurologic complications are common in patients hospitalised with COVID-19 infection. Most common complications are myalgias, headaches, encephalopathy and dizziness. Uncommon complications are stroke, motor and sensory deficits, seizures, ataxia and movement disorders. Multiple neuro-ophthalmological manifestations have also been reported in association with COVID-19. These complications may be the result of a range of pathophysiological mechanisms like hypoxic neuronal injury during active COVID-19 infection, RAS dysfunction, immune dysfunction and direct injury by the virus etc throughout the course of the disease. Here we reported a case of neuro-ophthalmic complication of Idiopathic intracranial hypertension (IIH) followed by bilateral optic atrophy in a middle-aged man with recent COVID-19 infection. He presented to the emergency with complaints of headache, dizziness and sudden painless bilateral diminution of vision for 3 days. His fundus examination was suggestive of bilateral papilledema, his MRI brain was normal and opening pressure of CSF was raised on lumbar puncture. His MRV was normal, there was no evidence of CSVT. He was started on steroids and acetazolamide. His headache improved but there was no improvement in visual acuity. Repeat fundus showed pale disc and MRI orbit was suggestive of bilateral optic atrophy.